Laporan Keuangan untuk Menilai Kinerja Penjualan Perusahaan PT Ace Hardware Indonesia Tbk Tahun 2019-2020 - Ichwan Ichwan; Sri Agustin (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Financial reports are one source of information used by management to assess company performance through financial reports with one of the objectives of making decisions and producing quality decisions. The purpose of this study is to analyze and discuss financial statements to assess the company's sales performance. Companies that are assessed for the performance of their financial statements are PT. Ace Hardware Indonesia Tbk. The method used in this research is descriptive qualitative with secondary data sources. Data collection and analysis techniques used in this research are documentation techniques in the form of financial reports published through official accounts at https://corporate.acehardware.co.id/id /annual balance sheet and income statement for the years 2019-2020. The results of this study are that in 2019 sales growth displayed results that were in line with expectations, namely with an increase in sales of 12.5% ​​and SSG 5.5% same store sales growth. until it reaches the share with the highest price of Rp. 1,920 in July 2019. In 2020 In general, the Company's performance received a significant impact due to the Covid-19 pandemic. The Company experienced a decrease in sales of around 9.0%, which was caused by a decrease in the flow of visitors at the outlets and the number of transactions. On the other hand, operating profit also decreased by 30.0% because operating cost efficiency was not able to cover the decline in sales. Keywords: Financial Report, sales performance